Determinants of People's Interest in Paying Zakat - Ladewi, Yuhanis (Asosiasi Dosen Akuntansi Indonesia, 2024)
This research aims to test the influence of awareness, knowledge, and belief variables on interest in paying zakat. This descriptive and associative research surveyed Muzakki in Palembang City. The research sample of 37 respondents used in this research was drawn based on purposive sampling. The results of this research prove that knowledge, religiosity, and awareness partially influence Muzakki's interest in paying zakat. Meanwhile, trust has no effect on Muzakki's interest in paying zakat